2000
DOI: 10.1046/j.1439-0442.2000.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Restraint Immobilization Stress on the Concentration of Bioamines and Cortisol in Plasma of Pietrain and Duroc Pigs

Abstract: Forty-five Duroc (recognized as not susceptible to stress) and 34 Pietrain (susceptible to stress) pigs were subjected to immobilization stress in a prone position for 5, 15, 30 and 60 min. Plasma concentrations of epinephrine (E), norepinephrine (NE), dopamine (DA) and cortisol (C) were determined in response to restraint stress. The concentrations of E, NE and DA were different between the two strains of pigs (some significant interactions); the highest response was seen after 5 min of stress. The concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
2
25
0
1
Order By: Relevance
“…These results confirm and extend previous descriptions of variations in HPA axis activity and reactivity in different lines of pigs, the largest differences being measured between White breeds (low concentrations) and Meishan pigs or wild boars (high concentrations) (Bergeron et al, 1996;Dé sauté s et al, 1997 and1999;Hay and Mormè de, 1998;Weiler et al, 1998;Rosochacki et al, 2000;Wise et al, 2001). It is worth noting that there was no significant difference (on a log scale) between genetic lines in the response to transportation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results confirm and extend previous descriptions of variations in HPA axis activity and reactivity in different lines of pigs, the largest differences being measured between White breeds (low concentrations) and Meishan pigs or wild boars (high concentrations) (Bergeron et al, 1996;Dé sauté s et al, 1997 and1999;Hay and Mormè de, 1998;Weiler et al, 1998;Rosochacki et al, 2000;Wise et al, 2001). It is worth noting that there was no significant difference (on a log scale) between genetic lines in the response to transportation.…”
Section: Discussionsupporting
confidence: 90%
“…This proportion was much lower within lines (up to 7%), eventually because less polymorphic genes are segregating within than across lines. The Pié train line used in the present study does not fit in this general scheme, with its relatively high concentrations of cortisol, similar to the concentrations found in Duroc pigs (Rosochacki et al, 2000), despite its extreme leanness. One explanation may be that the corticosteroid receptors that mediate the metabolic effect of cortisol are relatively insensitive to their ligand; it would also explain the absence of correlation between cortisol concentrations and carcass composition in the Pié train line.…”
Section: Discussionmentioning
confidence: 54%
“…At the day 136 serum cortisol levels of both HT and CT treatments showed a significant decrease (P<0.05), as compared to the previous measure (day 45, 128 days of age). Similar results were also obtained by Cook et al 13 , De Jong et al 14 and Rosochacki et al 10 , who observed the variation in the blood cortisol in response to several stressors related to modern swine production. It is important to have in mind that some variation occurs even in normal situations, as in the comfort temperature range, and the establishment of precise data is necessary to recognize the differences between normal periodical variation and physiological responses to stressors.…”
Section: Resultssupporting
confidence: 87%
“…Different responses of plasma cortisol were observed in Duroc and Pietrain pigs submitted to restraint immobilization from 5 to 60 minutes, with significant interaction between strain of animal and time to exposure to stress. 10 Several studies indicate that cortisol is susceptible to changes in serum concentrations when temperature is above the thermoneutral range and that can be likely used as an indicator of loss of welfare. The present study was designed to investigate the influence of chronic exposition to high temperature on serum cortisol level and if this measure can be used as an indicator of heat stress for growing-finishing pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focusing on both miniature pigs and the baseline immune traits in stressed pigs have been conducted (Desautes et al 1999;Rosochacki et al 2000;Wang et al 2009). However, the findings of these various authors are conflicting and difficult to reconcile into universally applicable theories.…”
Section: Introductionmentioning
confidence: 99%